Hand Hygiene among Hospital Staff: A Survey of Knowledge, Attitude, and Practice in A General Hospital in Syria - Cornelis Jonker; Maha Othman (Jurnal Keperawatan Indonesia, 2018)
Poor hand-hygiene adherence endangers the safety of both healthcare workers and patients. A cross-sectional Knowledge Attitudes Practicing (KAP) survey (n= 268) and an observation of hand-hygiene compliance (n= 36) were conducted among staff in a general hospital in Syria. The aim of this study was to investigate the degree of compliance with hand hygiene protocols by general health care workers including their knowledge, attitude and practice. The mean overall observed hand-hygiene compliance rate was 45.7% (95% CI 37.1 – 54.3). Nurses were observed to have better compliance than physicians. Staff were observed to be more concerned in performing hand-hygiene after than before patient contact (before mean= 32.0%, after mean= 51.2%, p< 0.05). The questionnaire showed that there was a significant correlation between knowledge, attitude, and facilities on the one hand and poor self-reported adherence on the other. Multivariate analysis showed that poor adherence was statistically significantly associated with males (63.5%), untrained staff (58.5%) and unavailability of washing basins (60.4%).  Poor adherence was high in ICU, among younger and unaware participants. Keywords: compliance, hand hygiene, hospital acquired infection, healthcare workers, Knowledge-Attituded-Practice (KAP), patient safetyAbstrak Kepatuhan pada kebersihan tangan yang buruk membahayakan keselamatan tenaga kesehatan dan pasien. Survei potong lintang Pengetahuan Sikap Praktek (n= 268) dan observasi kepatuhan kebersihan tangan (n= 36) dilakukan di antara staf di rumah sakit umum di Suriah. Tujuan dari penelitian ini adalah untuk mengidentifikasi tingkat kepatuhan dengan protokol kebersihan tangan oleh tenaga kesehatan termasuk pengetahuan, sikap dan praktik mereka. Rerata tingkat kepatuhan kebersihan tangan yang diamati secara keseluruhan adalah 45,7% (95% CI 37,1-54,3). Perawat diamati memiliki kepatuhan yang lebih baik daripada dokter. Staf yang diamati tampak lebih peduli melakukan kebersihan tangan setelah kontak dengan pasien dibanding sebelum kontak (rerata sebelum= 32,0%, rerata setelah= 51,2%, p< 0,05). Hasil kuesioner menunjukkan bahwa ada korelasi yang signifikan antara pengetahuan, sikap, dan fasilitas, namun disisi lain kepatuhan dilaporkan buruk. Analisis multivariat menunjukkan bahwa kepatuhan yang buruk secara statistik terkait secara signifikan dengan jenis kelamin laki-laki (63,5%), staf tidak terlatih (58,5%) dan tidak tersedianya tempat cuci tangan (60,4%). Tingkat kepatuhan yang rendah angkanya ditemukan cukup tinggi di ICU, di antara responden yang lebih muda dan tidak sadar. Kata Kunci: kebersihan tangan, kepatuhan, hospital acquired infection, tenaga kesehatan, keselamatan pasien, Pengetahuan-Sikap-Praktik